Impact of Price, Location, Facilities, and Product Quality on Customer Loyalty Through Customer Satisfaction - Panca Syahputra; Aqwa Naser Daulay; Budi Harianto (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
The research aims to analyze and test the impact of price, location, facilities, and product quality on customer loyalty through customer satisfaction. The novelty of this study is that it has more variables to be studied than its predecessors. This type of research is quantitative research with 100 samples and uses a method to analyze SEM-PLS with the help of Smart PLS 4.1.0.3 software. The test used is the outer model test, the inner model test and the hypothesis test, as well as the mediation test. Based on the validity test results and reliability test is declared valid and relieble. Research results show that facilities have a significant influence on customer loyalty, for price, location, product quality have no significant impact on client loyalty. Price variables, facilities, product quality have a significant influence on customer satisfaction, whereas location on client satisfaction has no significant impact. For customer satisfaction on customer loyalty has a significant influence. Mediation tests on client satisfaction variables influence the price, facilities, and quality of products on customer loyalty, whereas for location on client loyalty there is no influence to be mediated by customer satisfaction.